New Environmentally-Friendly and Sustainable Materials - Rodrigues, Alisson Mendes; de Araujo Neves, Gelmires; Menezes, Romualdo Rodrigues (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
One of the great challenges of contemporary society is establishing a sustainable way of life in harmony with the environment without compromising economic growth and technological development. On the other hand, the increase in the world population has driven per capita consumption, and consequently, the generation of waste. Because of this, new materials are being developed from different types of waste. This Special Issue aims to highlight and share recent scientific findings in the area of "New Environmentally Friendly and Sustainable Materials" manufactured from different material types (polymers, ceramics, metallics, and composites) and urban, industrial, mining and agricultural wastes. Moreover, scientific topics such as improving performance and durability, materials characterization, hybrid materials, foams and porous materials, trends and advances, and mechanical, electrical, magnetic, optical, and thermal properties will also be accepted.